Utility of the PedsQL Rheumatology Module as an Outcome Measure in Juvenile Fibromyalgia1. Issue 11 (28th October 2013) - Joffe, Naomi E.; Lynch‐Jordan, Anne; Ting, Tracy V.; Arnold, Lesley M.; Hashkes, Philip J.; Lovell, Daniel J.; Passo, Murray H.; Powers, Scott W.; Schikler, Kenneth N.; Kashikar‐Zuck, Susmita
<x xml:space="preserve">Abstract</x> Objective The PedsQL rheumatology module is currently the only available measure of disease‐specific quality of life for children and adolescents with juvenile fibromyalgia (FM), but limited information has been published about the psychometric properties of the instrument, specifically in juvenile FM. The objective of this study was to assess the reliability, validity, and sensitivity to change of the 5 scales (pain and hurt, daily activities, treatment, worry, and communication) of the patient and parent proxy versions of the PedsQL rheumatology module in the context of a randomized controlled trial in juvenile FM. Methods The entire PedsQL rheumatology module was administered as a supplementary outcome measure at baseline, posttreatment, and 6‐month followup assessments of 114 children and adolescents with juvenile FM enrolled in a trial testing the efficacy of cognitive–behavioral therapy. Results Internal consistency reliabilities for the scales were adequate to strong (Cronbach's α = 0.68–0.86). Parent proxy and child reports on most scales (except for daily activities and communication) showed moderate correlations (Spearman's r = 0.33–0.45). Support for construct validity was found by comparing child and parent reports with other related measures of pain and functioning (visual analog scale pain ratings and the Functional Disability Inventory). Finally, sensitivity to change was demonstrated by significant changes in 4 of the 5 scales (excluding the daily activities scale) after treatment. Conclusion The PedsQL rheumatology module generally appears to have good utility for use in juvenile FM patients, but there are some caveats to the interpretation of specific scales in this population.